A Case Study:Efforts for Improvement in Attainment of Course Outcomes in Control System Engineering - Sharma, Megha; Phadke, Arati S. (Journal of Engineering Education Transformations, 2025)
In Outcome Based Education, defining Course Outcomes, content delivery and evaluation methods complement each other resulting in effective learning. Study of Control systems is vital in Electronics Engineering so that the graduate develops ability to design a system, component, or process to meet desired stability needs. However, in Electrical Networks and Control System Engineering it is experienced that students find it difficult to understand concepts of frequency domain analysis. and control system components. The related course outcomes attainment is less than the expected level. This paper focuses on detailing the methods used to attain the course outcomes by linking the two courses viz. Electrical Networks and Control System Engineering. It also discusses the effect on performance of students in Control System Engineering course after improvisations in content delivery and assessment tools.The feedback of students shows that students are motivated to learn better with this approach.